2019
DOI: 10.3390/jcm9010062
|View full text |Cite
|
Sign up to set email alerts
|

Degenerative Cervical Myelopathy in Higher-Aged Patients: How Do They Benefit from Surgery?

Abstract: Background: Degenerative cervical myelopathy (DCM) is the most common reason for spinal cord disease in elderly patients. This study analyzes the preoperative status and postoperative outcome of higher-aged patients in comparison to young and elderly patients in order to determine the benefit to those patients from DCM surgery. Methods: A retrospective analysis of the clinical data, radiological findings, and operative reports of 411 patients treated surgically between 2007 and 2016 suffering from DCM was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Surgery can improve motor deficits and decrease nursing care requirements among elderly patients with DCM [31]. Therefore, early surgery might be the treatment of choice to interfere the natural history of DCM and improve the neurological prognosis [15,16,18,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgery can improve motor deficits and decrease nursing care requirements among elderly patients with DCM [31]. Therefore, early surgery might be the treatment of choice to interfere the natural history of DCM and improve the neurological prognosis [15,16,18,21].…”
Section: Discussionmentioning
confidence: 99%
“…Several predictors like duration of symptoms, high signal intensity (SI) on T2-weighted MRI, preoperative modified Japanese Orthopedic Association Score (mJOA Score), age, comorbidities, or smoking status were identified over the recent years to influence the neurological outcome of DCM patients. Interestingly, other factors like the type of stenosis, the number of affected levels, ventral or posterior approach or the type of surgical treatment do not affect the postoperative neurological outcome [13][14][15][16][17][18]. To our best knowledge, first symptom of DCM was not evaluated as a possible predictor of neurological outcome after surgery in detail.…”
Section: Introductionmentioning
confidence: 99%
“…While it is unclear if age is a negative predictor of neurological outcome, specific studies on older patients with DCM undergoing surgery have been shown that these patients clearly benefit from surgery, indicating that while older patients may not reach the same neurological recovery and may have more complications due to their age, they can have substantial improvement in neurological function after surgery (29,33).…”
Section: Agementioning
confidence: 99%
“…The editors of the issue contributed to this introductory review and decided to limit each of the past, present, and future sections to three themes in an effort to stay focused on the most important topics. The remaining 11 articles included 9 research papers and 2 systematic reviews focusing on different aspects, ranging from genetic factors [ 6 ] to clinical assessments [ 7 , 8 ], imaging [ 9 , 10 ], sagittal balance [ 11 ], surgical treatment [ 12 ], and outcome prediction [ 13 , 14 , 15 , 16 ] ( Table 1 ). These articles represented contributions from a diverse group of researchers coming from multiple countries, including Switzerland, Germany, Italy, United Kingdom, United States, South Korea, and Canada.…”
mentioning
confidence: 99%
“…It was interesting to note that patients with and without GICs were not considerably different from a neurological function perspective, however, patients with GICs presented with a unique set of diverging characteristics including that they were more commonly female, and nearly a third of patients suffered from psychiatric comorbidities. Gembruch et al [ 15 ] and Wilson et al [ 16 ] focused on surgical outcomes for older patients and collectively showed that older patient clearly benefit from surgery, but may benefit less due to worse baseline neurologic function. Janssen et al [ 12 ] reported a group of DCM patients in the context of rheumatoid arthritis, finding from their limited series that patients experience meaningful improvements in neurological function.…”
mentioning
confidence: 99%